2000
DOI: 10.1046/j.1525-1446.2000.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

The Crisis Nature of Health Care Transitions for Rural Older Adults

Abstract: The complex health, socioeconomic, and environmental problems experienced by many American elders often place them at high risk for disease and disability. Over time, acutely or chronically ill older persons experience numerous transitions across various health care settings. Although availability of health services is improving in rural areas, barriers such as distance, geography, and poor distribution often limit access to health care. In a longitudinal rural ethnography, the health care transition experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 15 publications
2
49
0
4
Order By: Relevance
“…Prior research has found that older people tend to experience health care transitions as difficult, and the decision to seek hospital care is often made hastily because of acute illness. 16 Further, the majority of community dwelling older persons as well as home health care patient seem to prefer treatment at the hospital as compared to treatment at home. 17,18 Another study including older people receiving home health care due to CHF or chronic obstructive pulmonary disease, found that these older adults viewed home care as a service with limited health care resources, not capable of treating acute illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that older people tend to experience health care transitions as difficult, and the decision to seek hospital care is often made hastily because of acute illness. 16 Further, the majority of community dwelling older persons as well as home health care patient seem to prefer treatment at the hospital as compared to treatment at home. 17,18 Another study including older people receiving home health care due to CHF or chronic obstructive pulmonary disease, found that these older adults viewed home care as a service with limited health care resources, not capable of treating acute illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Across social and health geography, studies illustrate, for example,'behavioural momentums' whereby for example, one human activity (such as drinking alcohol, taking drugs or undertaking casual labour) leads onto another (such as casual sex) with health implications (such as Hepatitis or HIV transmission) (Luginaah 2008;Mkandawire, et al 2014). In studies of ageing, however, human momentums are typically less behavioural and more circumstantial, either about the momentums that build as older people move -or are moved -spatially between care settings and services of increasing comprehensiveness in line with their changing physical and mental health (although studies focus primarily on the transitions themselves and their consequences (Magilvy et al, 2000;Reed et al, 2003;Lee et al, 2013). Elsewhere the momentums in the daily lives of people with chronic health conditions are a popular concern of social and health geography (Moss, 1997;Moss et al, 2003), these studies conveying how, in many cases, people' s lives might be more appropriately characterized by being'stuck'or'immobile'(lacking in momentum) or indeed'shrinking' (possessing momentum in an unwanted and reverse direction) (Dyck, 1995;Crooks 2007).…”
Section: Current Engagements With Human Movements: Key Empirical Themesmentioning
confidence: 99%
“…Magilvy et al (24) sostienen que en América la salud mejora, pero barreras como la distancia, la geografía y la pobre distribución de servicios y el cuidado de la salud hacen que el acceso se limite, especialmente para las personas de la tercera edad, quienes además de las barreras de acceso físicas que enfrentan, tienen limitaciones funcionales, escasos ingresos, alto riesgo de enfermedades, condiciones médicas de cuidado y limitaciones en el transporte que se suman a las demás barreras.…”
Section: Introductionunclassified
“…Cerca de la mitad de la población del mundo vive en áreas rurales, en condiciones de pobreza más acentuadas que en las áreas urbanas, con distancias más largas que recorrer hasta los sistemas de salud. Los recursos públicos de la salud dan soporte a las actividades diseñadas para promover la salud y prevenir la enfermedad, además del recurso profesional en diferentes áreas que pueda atender la mayoría de las necesidades de una población en el tiempo adecuado (24)(25)(26).…”
Section: Introductionunclassified